Internal career orientations guidance for emerging adults in a university of technology - Margaret M. Ngope; Melinde Coetzee (African Journal of Career Development, 2023)
Background: Schein’s career orientations inventory (COI) is known to help undergraduate emerging adults develop deeper insight into the master career values that drive study and career choices.